The isolation of Aspergillus fumigatus from wild Pink-footed Geese in England and Scotland - Beer, J V (Wildfowl, 1957)
A swab was devised that could be used on a large scale in the field to determine if the wild Pinkfoot carried spores or mycelium of Aspergillus fumigatus internally. A selective growth medium based on Czapek-Dox broth allowed the fungus to grow freely with little or no competition from other micro-organisms. Swabbing of the mouth and pharynx of 1188 apparently healthy Pinkfeet over three seasons produced 86 (7.2%) positive cultures of A. fumigatus. Controls showed that the technique used was adequate despite the relatively primitive field conditions. No significant difference was found between the three seasons nor between adults and juveniles. However, male Pinkfeet are more likely to harbour the fungus than females. The percentage of positives increased as the season progressed, and there was some evidence to suggest an east-west gradient across the country. The fungus found was probably derived form the soil and vegetation rather than the internal organs of the birds.